THE NEED TO EDUCATE STUDENTS IN THE SPIRIT OF GENDER EQUALITY (Multidisciplinary Journal of Science and Technology, 2024)
This article analyzes the introduction of the concept of gender into science, gender equality, gender issues in social life in the Republic of Uzbekistan, and the political and social situation of gender equality relations. Also, the specific aspects of the implementation of the gender approach to the higher education system, the creation of equal rights and opportunities for women and men in higher education are interpreted from a scientific point of view.